Sensor technologies for the detection and monitoring of endocrine-disrupting chemicals - Shah, Muhammad Musaddiq; Ahmad, Khurshid; Boota, Sonia; Jensen, Tor; La Frano, Michael R.; Irudayaraj, Joseph (Frontiers in Bioengineering and Biotechnology, 2023)
Endocrine-disrupting chemicals (EDCs) are a class of man-made substances with potential to disrupt the standard function of the endocrine system. These EDCs include phthalates, perchlorates, phenols, some heavy metals, furans, dimethoate, aromatic hydrocarbons, some pesticides, and per- and polyfluoroalkyl substances (PFAS). EDCs are widespread in the environment given their frequent use in daily life. Their production, usage, and consumption have increased many-fold in recent years. Their ability to interact and mimic normal endocrine functions makes them a potential threat to human health, aquatics, and wild life. Detection of these toxins has predominantly been done by mass spectroscopy and/or chromatography-based methods and to a lesser extent by biosensor approaches, such as electrochemical and/or colorimetric methods. Instrument-based analytical techniques are often not amenable for onsite detection due to the lab-based nature of these detecting systems. Alternatively, analytical approaches based on sensor/biosensor techniques are more attractive because they are rapid, portable, equally sensitive, and eco-friendly. Advanced sensing systems have been adopted to detect a range of EDCs in the environment and food production systems. This review will focus on advances and developments in portable biosensing techniques for EDCs, encompassing electrochemical, colorimetric, optical, aptamer-based, and microbial sensing approaches. We have also delineated the advantages and limitations of some of these sensing techniques and discuss future developments in sensor technology for the environmental sensing of EDCs.